Delay discounting and self‐reported impulsivity in adolescent smokers and nonsmokers living in rural Appalachia. (3rd June 2015) - Lewis, Russell; Harris, Millie; Slone, Stacey A.; Shelton, Brent J.; Reynolds, Brady
<x xml:space="preserve">Abstract</x> Background and Objectives This study evaluated whether impulsivity (delay discounting and BIS‐11‐A) is associated with adolescent smoking status in a region with strong environmental risk factors for smoking. Methods Forty‐two adolescent smokers and nonsmokers from rural Appalachia completed discounting and self‐reported impulsivity assessments. Results The BIS‐11‐A, but not the measure of discounting, was associated with smoking status; however, neither assessment predicted smoking status once parent/best‐friend smoking variables were statistically accounted for. Discussion and Conclusions In regions with strong environmental risk factors for smoking, delay discounting may play a more limited role in risk of initiation. Scientific Significance Helps to better define impulsivity as risk factors for smoking in relation to familial and broader cultural variables. (Am J Addict 2015;24:492–494)